The Contribution of Islamic Religious Education Teachers’ Social Competence in Enhancing Students’ Learning Motivation at Al Kautsar Senior High School and Al-Azhar Senior High School in Bandar Lampung - A. Ikhlas Muhtar Hadi; Imam Syafi'i; Ali Murtadho (al-Afkar, Journal For Islamic Studies, 2026)
The development of technology and the evolving characteristics of adolescents in the modern era require teachers not only to possess pedagogical competence but also adequate social competence in establishing harmonious, communicative, and inspiring interpersonal relationships. As Islamic-based educational institutions in Bandar Lampung, SMA Al-Kautsar Bandar Lampung and SMA Al-Azhar Bandar Lampung exhibit distinctive religious characteristics that are relevant to be examined, particularly in the context of the contribution of Islamic Religious Education (PAI) teachers’ social competence to students’ intrinsic and extrinsic motivation. This study employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation. The data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that the social competence of PAI teachers in both schools is categorized as good, as reflected in effective communication skills, empathetic attitudes, openness, and exemplary behavior in social interactions. Students’ learning motivation, both intrinsic and extrinsic, is also categorized as good. The findings suggest that teachers’ social competence contributes positively to enhancing students’ learning motivation, as harmonious interpersonal relationships are able to create a conducive, participatory, and meaningful learning environment. Based on these findings, future research is recommended to examine more deeply the influence of teachers’ social competence using quantitative or mixed methods approaches in order to obtain more measurable levels of effect. Furthermore, future studies may be expanded to different educational levels or other relevant variables, such as teachers’ personality competence, learning environment, and the role of technology in enhancing students’ learning motivation.